2020
DOI: 10.1039/d0pp00304b
|View full text |Cite
|
Sign up to set email alerts
|

Everlasting rhodamine dyes and true deciding factors in their STED microscopy performance

Abstract: The authors took an independent and closer look at the family of red-emitting rhodamine dyes known for a decade due to their excellent performance in STED microscopy. After the family...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(45 citation statements)
references
References 58 publications
1
44
0
Order By: Relevance
“… a Relative quantum yields measured in PBS buffer at pH = 7.4, using oxazine 170 as a reference dye ( 9 ). b See Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Relative quantum yields measured in PBS buffer at pH = 7.4, using oxazine 170 as a reference dye ( 9 ). b See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous comparative study investigated the STED applications of red-emitting rhodamine dyes, demonstrating that fluorophore functionalization with charged polar functional groups (sulfate, phosphate) was crucial for the dye’s performance ( 9 ). However, although a large set of dyes was tested, positively charged compounds were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…First, it may be caused by aggregation of the close-by markers that may not only quench the emission but even prevent on-switching. Possible remedies are based on the incorporation of charged side groups (e.g., sulfonates) 64 or reducing the DOL values. The first option is already implemented in our DAEs having charged trimethylammonium groups, and the second one is inappropriate as it should result in dimmer images or longer recording times.…”
Section: Resultsmentioning
confidence: 99%
“…114 In this context, it is also important to highlight that the photostability and other fluorogenic properties of the STED-compatible red-emitting rhodamine dyes could be adequately modulated by attaching small-molecule intramolecular stabilizing agents and/or auxiliary groups at different sites of the rhodamine-based fluorescent probes. 115…”
Section: Xanthene- Cyanine- Oxazine- and Bodipy-based Fluorophores Fo...mentioning
confidence: 99%
“…114 In this context, it is also important to highlight that the photostability and other fluorogenic properties of the STED-compatible red-emitting rhodamine dyes could be adequately modulated by attaching small-molecule intramolecular stabilizing agents and/or auxiliary groups at different sites of the rhodamine-based fluorescent probes. 115 Song et al reported the synthesis of some modified Sirhodamine (SiRMO) dyes, in which methoxybenzene units were incorporated into the xanthene moieties. 116 One of the newly synthesized Si-rhodamine dye (SiRMO-2) containing the 2,6dimethoxybenzene substituent, not only showed increased brightness but also possessed markedly improved stability owing to steric hindrance protection mediated by two methoxy groups on the ninth carbon atom of the xanthene (Fig.…”
Section: Bodipymentioning
confidence: 99%